Phytoestrogen Genistein Protects Against Endothelial Barrier Dysfunction in Vascular Endothelial Cells Through PKA-Mediated Suppression of RhoA Signaling - Jia, Zhenquan (Endocrine Society, 2013)
The soy-derived phytoestrogen genistein has received attention for its potential to improve vascular function, but its mechanism remains unclear. Here, we report that genistein at physiologically relevant concentrations (0.1–10 μM) significantly inhibited thrombin-induced increase in endothelial monolayer permeability. Genistein also reduced the formation of stress fibers by thrombin and suppressed thrombin-induced phosphorylation of myosin light chain (MLC) on Ser(19)/Thr(18) in endothelial cells (ECs). Genistein had no effect on resting intracellular [Ca(2+)] or thrombin-induced increase in Ca(2+) mobilization. Addition of the inhibitors of endothelial nitric oxide synthase or estrogen receptor did not alter the protective effect of genistein. RhoA is a small GTPase that plays an important role in actin-myosin contraction and endothelial barrier dysfunction. RhoA inhibitor blocked the protective effect of genistein on endothelial permeability and also ablated thrombin-induced MLC-phosphorylation in ECs. Inhibition of PKA significantly attenuated the effect of genistein on thrombin-induced EC permeability, MLC phosphorylation, and RhoA membrane translocation in ECs. Furthermore, thrombin diminished cAMP production in ECs, which were prevented by treatment with genistein. These findings demonstrated that genistein improves thrombin-induced endothelial barrier dysfunction in ECs through PKA-mediated suppression of RhoA signaling.